Preserving soil properties and enhancing cauliflower yield with black plastic mulch in Bangladesh - Farhana Akter Mitu; Mohammad Ashraful; Mohammad Abdul Kader; Fakhar Uddin Talukder; Tahmina Akter; Nargis Akter; Jahidul Karim; Rajesh Kumar Soothar; Ashutus Singha (Universitas Sebelas Maret, 2025)
Poor soil health and inefficient farming practices significantly challenge sustainable agriculture and crop productivity in Bangladesh. This study evaluated the impact of various mulching techniques on soil properties, cauliflower yield, and carbon sequestration in Bangladesh to identify the optimal mulching strategy for sustainable cauliflower production and carbon sequestration. A field experiment in the Bogura district evaluated the effects of various mulching materials—newspaper, rice husk, rice straw, black plastic, craft paper, and no mulch—on soil physicochemical properties and cauliflower production. Data measurement and monitoring assessed soil properties, mulch degradation rates, and cauliflower quality, with organic carbon determined using Walkley and Black's method. Results showed significant impacts of mulching on soil parameters and cauliflower yield. Black plastic mulch increased soil temperature by approximately 6°C and conserved soil moisture by 13.2% compared to the no-mulch (control). Organic mulches, especially rice husk, were superior in conserving soil carbon (21.3 g Kg-1) and increasing available nitrogen (22.4 mg Kg-1), phosphorus (36.5 mg Kg-1), and soil pH (7.4). Although all treatments increased electrical conductivity (EC), the control showed the highest EC value (405.5 µS cm -1). Among organic mulches, craft paper had the highest degradation rate followed by newspaper and rice straw mulches. Cauliflower yield varied with mulch type, with black plastic producing the highest yield (1162.0 g), followed by rice straw (1050.0 g), rice husk (983.0 g), craft paper (821.0 g), and newspaper (752.0 g). These findings suggested black plastic mulch for maximizing cauliflower production in Bangladesh and similar conditions.